Observational Relationship Between Entrainment Rate and Environmental Relative Humidity and Implications for Convection Parameterization. Issue 24 (18th December 2018) - Lu, Chunsong; Sun, Cheng; Liu, Yangang; Zhang, Guang J.; Lin, Yanluan; Gao, Wenhua; Niu, Shengjie; Yin, Yan; Qiu, Yujun; Jin, Lianji
Abstract: Entrainment rate is a critical but highly uncertain quantity in convective parameterizations; especially, the effects of environmental relative humidity on entrainment rate are controversial, or even opposite, in different studies. Analysis of aircraft observations of cumuli from the Routine AAF (Atmospheric Radiation Measurement [ARM] Aerial Facility) Clouds with Low Optical Water Depths (CLOWD) Optical Radiative Observations (RACORO) and Rain in Cumulus over the Ocean (RICO) field campaigns shows that entrainment rate is positively correlated with relative humidity. Physical analysis shows that higher relative humidity promotes entrainment by reducing buoyancy in the cloud cores and by weakening downdrafts near the cloud cores. The reduced buoyancy in the cloud cores and weakened downdrafts surrounding the cores further reduce updrafts in the cloud cores; the cloud cores with smaller updrafts are more significantly affected by their environment, resulting in larger entrainment rate. The relationship between entrainment rate and relative humidity is consistent with the buoyancy sorting concept widely used in convection parameterizations. The results provide reliable in situ observations to improve parameterizations of entrainment rate. Plain Language Summary: Cumulus clouds affect vertical distributions of atmospheric energy and mass and further affect weather and climate. Near cloud edges, environmental air can be entrained into clouds. Entrainment rate describes how fast environmental air is entrained, which affects the growth and dissipation of clouds. However, our understanding of the factors affecting entrainment rate is far from established. Especially, different studies found that the effects of environmental relative humidity on entrainment rate could be opposite. Based on in situ observations of cumulus clouds, it is found that higher relative humidity causes larger entrainment rate. Physical analysis shows that relative humidity affects entrainment rate through its effects on thermodynamic and dynamical structures in and outside cumulus clouds. Mathematical artifacts in the calculation of entrainment rate are ruled out. Key Points: Entrainment rate is found to be positively correlated with relative humidity based on in situ observations for the first time Physical mechanisms underlying the relationship between entrainment rate and relative humidity are examined Mathematical artifacts affecting the relationship between the two quantities are ruled out